O uso de agrotóxicos no município de Parintins-AM: uma análise espaço-temporal entre os anos de 2006 e 2017 - Alencar, Ageu Pinheiro (Brasil, 2025)
Over the past few decades, there has been a significant increase in the use of pesticides in rural areas, leading to intoxication problems among farmers due to a lack of knowledge about their proper application. The objective of this thesis was to investigate the space time dynamics of pesticide use in the municipality of Parintins, State of Amazonas, during the first two decades of the 21st century. To achieve this, a methodology based on qualitative and quantitative approaches was used, including analysis of geo-statistical data from the Agricultural Censuses of the Brazilian Institute of Geography and Statistics (IBGE) from 2006 and 2017, as well as the production of tables and a literature review. In Parintins, pesticide use in agricultural establishments increased from 9% in 2006 to 19% in 2017. The study revealed growth in both family and non-family agriculture, with pesticide use rising from 8% to 20.89% in non-family establishments and from 9% to 18% in family establishments. In 2006, only 6% of the 810 establishments with technical guidance used pesticides, while in 2017, this number increased to 8% of the 268 establishments. However, not all the data from 2006 are available for 2017, making comparisons on this highly relevant topic difficult. Finally, the research aimed to contribute to strengthening the creation of public policies and educational actions to raise awareness among farmers about the risks of indiscriminate pesticide use. It is concluded that, in addition to intensifying the inspection and control of the commercialization of these products, it is essential to invest in training programs to guide farmers. In this way, the aim is to contribute to food security and the well-being of the population, while also preserving the environment.